Ruling on Prayer That Is Not in Accordance With the Direction Of The Qibla: Case Study of Mosques in Sidamanik District - Rizki Muhammad Haris (AT-TAFAHUM: Journal of Law, 2017)
The main problem in this paper is the difference in the direction of the Qibla among society, especially in Indonesian society, triggered by the change in the direction of the Qibla in the Indonesian region, which initially faced west and then northwest. With the advancement of technology at that time This makes determining the direction of the Qibla easy, as facing the Qibla is a valid requirement for performing prayer; there is no difference of opinion among scholars on this matter. Imam Shafi'i is of the opinion that one must face the Qibla correctly. If one is wrong, one must repeat the prayer once and for all. Another opinion states that there is no need to repeat a prayer once it has already been performed, as long as it is not intentional and does not negate efforts to find the correct direction of the Qibla. This is the opinion of Imam Malik and Abu Hanifah. However, in this case, Imam Malik recommends repeating the prayer (with the wrong direction of the Qibla) at its proper time.